Polypharmacotherapy in Institutionalized Epileptic Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
An attempt to minimize polypharmacotherapy, to discontinue the use of phenobarbital, and to assess the relation between drug levels and antiepileptic effect in institutionalized severely retarded children is reported from the Department of Pediatrics, St.